SISTEMAS DE TRATAMENTO DE ÁGUAS CINZA: DIFERENTES MÉTODOS DE TRATAMENTO (REMUNOM, 2024)
It is widely recognized that water is not a renewable resource, and as mentioned, its availability is limited in various regions of the planet. The use of water in industries is increasing alongside population growth, driven by the need for production due to higher consumption rates. There is the possibility of developing an instantaneous and economically viable treatment for greywater through recirculation, allowing for the reuse of this water in single-family residences, thereby generating savings in water consumption. This study aims to conduct a literature review on the most widely discussed greywater treatment methods in the literature, with the purpose of evaluating their developments and efficiency. The methodology adopted was based on bibliographic research, focusing on finding relevant material on the chosen topic for the article. A vast amount of literature addressing greywater treatment and the various methods studied in laboratories around the world was identified. The wastewater treatments researched and improved over the years are categorized into primary, secondary, and tertiary treatments, each with its specific characteristics. Additionally, other methods such as septic tanks, anaerobic filters, and root zones are highlighted. Although there are programs, workshops, and training sessions focused on water management in Brazil, not all are centered on the treatment and reuse of domestic greywater. Therefore, it is necessary to conduct research on the relationship between society, environment, and technology, aiming for sustainable development that can meet the needs of the present without compromising the ability of future generations, through the integration of these elements into society.